Rekonstruksi Parenting Profetik Perspektif Gender dalam Desain E‑Modul Pembelajaran PG‑PAUD - Mokhammad Samson Fajar; Dian Ayuwita (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The increasing use of digital learning in early childhood education has not been accompanied by adequate integration of gender-responsive and value-based parenting perspectives. Many learning resources still present parenting concepts that are gender-biased and lack ethical-spiritual foundations, resulting in limited student understanding of equitable parenting practices. This study aims to develop a Prophetic Parenting E-Module with a gender perspective for the Early Childhood Parenting course and to examine its feasibility and effectiveness in improving students’ gender awareness and learning outcomes. The research employed a Research and Development (R&D) design using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation, student response questionnaires, and pretest–posttest learning assessments. The results indicate that the developed e-module achieved a high level of validity based on material, media, and gender-perspective experts. Student responses showed that the module was practical, engaging, and easy to use. Learning effectiveness testing revealed an increase in students’ understanding of gender-equitable parenting and prophetic values. The study concludes that the Prophetic Parenting E-Module is feasible and effective as a digital learning resource that integrates gender sensitivity and Islamic ethical values in early childhood parenting education.